The Romantic-Masculine Discourse About Feminine Virtue: Travesty Ventriloquism, Literary Censorship, and Don Juan’s Like Violence in Montalvo and Mer - Grijalva, Juan Carlos (2010)
The author revises the discourse of Juan Montalvo in two texts: Las Catilinarias and El Regenerador, indicating the strategies employed to exercise patriarchal control over women: he simulates a feminine voice which speaks with and for women about their own needs and desires; he censures and restricts the feminine creative poetic ability; and sanctions those rebellious women who question his masculine authority. The author says that the “liberal Catholicism” of Montalvo in relation to the education of women is similar to the conservative and catholic ideology of his political enemy, president García Moreno. Likewise, en Ojeada Histórico-Crítica de la Poesía Ecuatoriana, Juan León Mera censures the author, the authority and the authorization to write about two ecuadorian poets (Dolores Veintimilla and Mercedes González de Moscoso) as a method to control and watch these manipulative, impulsive and sinful women; something similar happens as regards to the work of Sor Juana in Obras Selectas de la Célebre Monja de Méjico Sor Juna Inés de la Cruz. Finally, in his Geometría Moral Juan Montalvo goes one step further and reveals the egocentric and perverse masculine authority.